Penggunaan Surat Kuasa Membebankan Hak Tanggungan (SKMHT) dalam Perjanjian Kredit Perbankan pada Bank Perkreditan Rakyat (BPR) di Wilayah Kerja Bank Indonesia Jember - Nanang Tri Budiman; Tioma Roniuli Hariandja (Fakultas Hukum Universitas Islam Jember, 2013)
Each credit agreement will be followed by a collateral agreement . Therefore, the principal credit agreement is an agreement or agreement in principle , being a guarantee agreement is an agreement or accesoir follow , meaning there and the expiry of the guarantee depends on the credit agreement . Power of Attorney Charge Mortgage (SKMHT ) is an authorization issued by the Mortgage giver as to the recipient of the authorizing special power to charge an object with Mortgage . Mortgage Provision shall be made solely by the giver Mortgage by way appear before the PPAT . The deadline given by the Act for the manufacture SKMHT must be properly addressed , because it can lead to